Hesitancy and Acceptance of Covid-19 Vaccine on Pregnant Women in Southeast Sulawesi, 2021 - Juminten saimin; Lianawati Lianawati; Monovalentino Monovalentino; Nur Indah Purnamasari; Steven Ridwan (Halu Oleo University, 2022)
Background: ITAGI has recommended the provision of the COVID-19 vaccine for pregnant women. Women are more hesitant than men on the COVID-19 Vaccine Acceptance Survey in Indonesia. Purpose: To determine the acceptance and doubt about the COVID-19 vaccine in pregnant women. Methods: This was a descriptive study, which was carried out in July-August 2021. The sample was pregnant women in Southeast Sulawesi. Data retrieval using a survey technique with a questionnaire in the google form with informed consent on the first page. Results: Pregnant women who are willing to receive the COVID-19 vaccine voluntarily are 43.6%, undecided 34.1%, and 22.3% are not willing. For pregnant women who are not willing and hesitant to receive the vaccine voluntarily, 29.1% are willing if required and 70.9% are still not willing. If they get privileges, 56.4% are willing and 43.6% are still not. Pregnant women worry about their babies, 84.2% for mothers who are willing to be vaccinated and 77.9% for mothers who are unsure and not willing to be vaccinated. Concerned about their pregnancy, pregnant women who are willing to be vaccinated are 79.7% and those who are doubtful and unwilling are 75%. Those who doubt the safety of the vaccine are 36.6%. Around 51.5% of pregnant women want to consult with doctors and health workers. The most preferred places for vaccination are doctors/midwives/private hospitals (47.2%) and Puskesmas (42.7%). Most pregnant women widely used (83.6%) and desired (70.2%) social media to get information. Conclusion: Acceptance of the COVID-19 vaccine in pregnant women is low. There are concerns of pregnant women about pregnancy and their fetus, as well as doubts about their safety. Massive information needs to be provided by doctors and health workers through social media and others that can be accessed by pregnant women.Keywords: acceptance, COVID-19, doubt, pregnant women, vaccine